2019
DOI: 10.1136/bmjopen-2018-026638
|View full text |Cite
|
Sign up to set email alerts
|

Extent and determinants of catastrophic health expenditure for tuberculosis care in Chongqing municipality, China: a cross-sectional study

Abstract: ObjectiveTo investigate the extent and associations of patient/diagnostic delay and other potential factors with catastrophic health expenditure (CHE) for tuberculosis (TB) care in Chongqing municipality, China.DesignA cross-sectional study.SettingFour counties of Chongqing municipality, China.ParticipantsA total of 1199 patients with active pulmonary TB beyond 16 years and without mental disorders were consecutively recruited in the four counties’ designated TB medical institutions.Outcome measuresThe inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 45 publications
1
27
0
1
Order By: Relevance
“…Only 35.6% of patients reported that they were diagnosed with suspected TB at their first visit, and the rest were informed that they had pneumonia, pleurisy, upper respiratory infection, and so on. Consistent with our study, other investigators pointed out that early diagnosis of TB reduced costs while achieving treatment success [29,30]. The total number of registered active TB cases were 1317, included 76(5.8%) native case and 1241(94.2%) migrant cases in Bao'an district in 2013 [31].…”
Section: Discussion Of Key Findingssupporting
confidence: 88%
“…Only 35.6% of patients reported that they were diagnosed with suspected TB at their first visit, and the rest were informed that they had pneumonia, pleurisy, upper respiratory infection, and so on. Consistent with our study, other investigators pointed out that early diagnosis of TB reduced costs while achieving treatment success [29,30]. The total number of registered active TB cases were 1317, included 76(5.8%) native case and 1241(94.2%) migrant cases in Bao'an district in 2013 [31].…”
Section: Discussion Of Key Findingssupporting
confidence: 88%
“…For example, Zhou C, etc. found that hospitalization is an important determinant of the occurrence of CHE [9], while in a study by Duan et al, despite observed strong association between hospitalization and CHE, the association was not statistically significant after adjusting for potential confounding factors (aOR:1.342, 95%CI: 0.950-1.897) [8]. The conflicting findings from two studies could probably resulted from the rates of patients participating in the New Cooperative Medical Scheme, an insurance specifically designed to cover more disadvantaged rural population.…”
Section: Introductionmentioning
confidence: 85%
“…To date, there have been few studies on catastrophic health expenditures (CHE) of TB patients under the designated hospital model in China, and the conclusions are not consistent [8,9]. For example, Zhou C, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 When a household must reduce its basic expenses over a period of time in order to cope with OOP payments, it is viewed as a catastrophic health expenditure (CHE). CHE is an index associated with the proportion of OOP payments that exceed a given threshold of the total household income (eg, 10%) 14,15 or the total household expenditures (eg, 40%) within a given year. 16 CHE may expose households to a significant risk of impoverishment and can result in economic burden for both developing and developed countries.…”
Section: Introductionmentioning
confidence: 99%